Effect of impregnation of silica into kenaf fibre- reinforced epoxy composites - Bajuri, Farid (2018)
Natural fibers are mechanically and thermally weaker than synthetic fibre due to its high water intake. To overcome this problem, addition of hydrophilic silica is expected to penetrate into the lumen and cell walls of fibre thus serving as blocking agent to inhibit water absorption. Two methods were adopted for the fabrication of hybrid epoxy reinforced with kenaf/silica: (1) Vacuum Infusion (VAC) and (2) Hand Lay-up/Hot Press (HP). For VAC process, the silica/epoxy solution was infused into fibre using vacuum pressure while for HP composites, silica/epoxy solution was spread onto fibre before hot pressed at 85˚C for 20 mins and cold pressed subsequently for another 5 mins. Another method was applied for HP which involves impregnation (IMP) of silica/epoxy solution into fibre. To achieve this, fibre was first degassed before submerged into silica/epoxy solution overnight and then compressed to remove excess resin prior to hot pressing the composite. Overall, the highest flexural strength and flexural modulus was achieved by IMP specimen of 40 vol% kenaf and 5 vol% silicas, with 78.8MPa and 5.11 GPa respectively. For HP specimens, the increment in kenaf volume leads to increase in flexural properties. In addition to that, the flexural strength and flexural modulus of HP specimens with 0, 1 and 5 vol% silica were found to be higher than VAC specimens. Despite that, water uptakes of VAC specimens were lower (lower water absorption rate is more desirable), ranging from 8-18.4% while HP specimens absorbs as much as 13-29%. Increment of kenaf volume was found to increase water uptakes considerably. On the other hand, inclusion of silicas also increased the water uptakes but only slightly. Interestingly, IMP specimens with 40, 50 and 60 vol% kenaf and 5 vol% silica absorbed 30.5, 36.7 and 54.4% less water respectively than their HP counterparts, indicating that silica has successfully impregnated the fiber walls and lumen thus blocking water from entering the fibres. Finally, the thermal stability of silica infused specimens was better due to the higher degradation temperature. Generally, composites with 40 vol% kenaf and 5 vol% silica had the highest degradation temperature at 335.43˚C for HP specimen while 60 vol% kenaf and 0 vol% silica HP composite possessed the lowest degradation temperature with 318.79°C.